ISOLASI ACTINOMYCETES DARI TANAH KEBUN SEBAGAI BAHAN PETUNJUK PRAKTIKUM MIKROBIOLOGI - Pujiati, Pujiati (Jurnal Florea, 2014)
The objective of this study was to isolate actinomycetes from soil of tea plantations, Jamus ngawi as a microbiology lab manual chapter isolation and characterization of microbes. The medium used is the medium of MHA and MHB. Soil samples taken to a depth of 10-15 cm from the surface with capture location is about 07o 4153,07 S and 111Â  37 24.64 E. The isolates were obtained observed morphologic characters include colony shape, colony color, surface characteristics of colonies, colony growth, colony elevation, and the edge of the colony. Isolatesof actinomycetes were successfully isolated are Streptomyces, Nocardia and Nocardiopsis. Actinomycetes isolates have been found that can be used as a collection of the microbiologylaboratory.Keywords : actinomycetes, soil of tea plantation, microbiology lab manual